Metamaterial Surface Plasmon-Based Transmission Lines and Antennas - Kianinejad, Amin (Springer Theses, Recognizing Outstanding Ph.D. Research,, 2018)
This thesis proposes a reliable and repeatable method for implementing Spoof Surface Plasmon (SSP) modes in the design of various circuit components. It also presents the first equivalent circuit model for plasmonic structures, which serves as an insightful guide to designing SSP-based circuits. Today, electronic circuits and systems are developing rapidly and becoming an indispensable part of our daily life; however the issue of compactness in integrated circuits remains a formidable challenge. Recently, the Spoof Surface Plasmon (SSP) modes have been proposed as a novel platform for highly compact electronic circuits. Despite extensive research efforts in this area, there is still an urgent need for a systematic design method for plasmonic circuits. In this thesis, different SSP-based transmission lines, antenna feeding networks and antennas are designed and experimentally evaluated. With their high field confinement, the SSPs do not suffer from the compactness limitations of traditional circuits and are capable of providing an alternative platform for the future generation of electronic circuits and electromagnetic systems.